Digital tools for the development of reading comprehension in distance learning - Quinto Román, Marino Cayetano (2021)
Objective. To determine the influence of digital tools on the development of reading comprehension in students of the second grade of secondary level, of the Ramón Castilla School of the district of Chuschi, in the remote education modality, 2020. Methods. The research was developed from the quantitative, explanatory type and experimental design in its quasi-experimental aspect. The sample, extracted from an intentional non-probabilistic sample, was made up of 32 students from sections A and B. The instrument used to collect the data consisted of a standardized test. Results. The participation of the 16 students of the experimental group, after the pre and post-test, showed that 7 (43.8%) students were placed in the level of achievement; 6 (37.5%), in process; 3 (18.8%), in outstanding achievement and 0 (0.0%), in initiation. After the hypothesis test using the Mann-Whitney U statistician, a significance value of 0.002 was obtained which is less than 0.05; it was shown that, at 95% reliability, digital tools influence reading comprehension. Conclusions. The study concludes that digital tools significantly influence the development of reading comprehension in students of the second grade of secondary level of the Ramón Castilla School of the district of Chuschi, in the remote education modality, 2020.